Palladium-Catalyzed and Quinazoline-Directed C–H Selective Acetoxylation of 2-Arylquinazolines - Wei, Song; Ouyang, Banlai; Deng, Zhihong; Yang, Qin; Peng, Yiyuan (Synthesis, 2019)
A series of acetoxylated 2-arylquinazolines have been successfully synthesized via the Pd-catalyzed and quinazoline-directed C–H activation/acetoxylation of the corresponding 2-arylquinazolines with iodobenzene diacetate in AcOH/Ac2O.
Keywords: 2-arylquinazoline; acetoxylation; transition-metal catalysis; C–H activation; iodobenzene diacetate